On CR-Lightlike Product of an Indefinite Kaehler Manifold - Rakesh Kumar; Jasleen Kaur; R. K. Nagaich (International Journal of Mathematics and Mathematical Sciences)
We have studied mixed foliate CR-lightlike submanifolds and CR-lightlike product of an indefinite Kaehler manifold and also obtained relationship between them. Mixed foliate CR-lightlike submanifold of indefinite complex space form has also been discussed and showed that the indefinite Kaehler manifold becomes the complex semi-Euclidean space.